Rozwój controllingu procesów w małych i średnich przedsiębiorstwach z wykorzystaniem benchmarkingu - Czyż-Gwiazda, Ewa (Evolution of the Process Controlling in SME's Using the Benchmarking., 2006)
The aim of this paper is to show how controlling system has evolved over the time and how enterprises could use benchmarking in process controlling to compare their performance with a chosen sample of companies. A good impulse for developing the process controlling in Poland was also the increasing number of quality management system certification. The results of benchmarking could be presented graphically which is very important from controllers' and management's view. The graphic presentation of the scores is possible when special tools are used. A good example for top management could be a new management tool called Benchmark Index available for Polish companies (especially for SME's) since last year. In Benchmark Index the data are collected using the five typical steps and the Balanced Scorecard model. That means that data come from four different perspectives: the financial perspective, the customer perspective, the internal process perspective and the learning and growth perspective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 23-33